IDN-Global dan Pendewasaan Diaspora Indonesia (2013-2015) - Nuryananda, Praja Firdaus (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis research proposes the idea that IDN-G, as a non-governmental institution, has been transforming the Indonesian diaspora posture in the context of globalization and nationalism. IDN-G has been a crucial part in giving positive discourse to Indonesian diaspora, improving Indonesian democracy, increasing the number of social philanthrophy, and in enforcing the dual citizenship law. On another hand, IDN-G takes role in encouraging Indonesian economy by remittance, investment, and organization. With the existence of IDN-G, Indonesian diaspora introduces a new form of Indonesian nationalism, which called long-distance virtual nationalism. It articulates Castell’s network society, Habermas’ virtual public sphere and Anderson’s long distance nationalism. Finally, IDN-G brings new characteristics on Indonesian diaspora, they are 1) Indonesian diaspora is not only labor migrant, 2) it contributes not only in economy, but also in social and politics, and 3) the diaspora is not state-driven, but it is society-driven.Keywords: IDN-Global, globalization, nationalism, virtual, Indonesian diasporaDOI:https://doi.org/10.33005/jgp.v3i02.1939